Los “Ferrocarriles Unidos de Yucatán”. Ensayos reorganizativos 1910-1942 - Anaya Merchant, Luis (El Colegio de México, A.C., 2024)
This essay shows a historical alternative that the United Railways of Yucatan could travel. It presents the reorganization project of 1942 analyzing circumstances, actors and expectations that fed it. For this purpose, two sections are developed that frame and precede said alternative; in them it realizes, among other points, the origins of the company, the tensions that gave birth to it, the first effects that the revolution imposed on it and that continued to overwhelm it, its dependence on the predominance of henequen, the fragility of its finances, the onerous weight of their “english debt” and the various subnational and federal efforts to revitalize them. The last section studies the financial basis of the private project of 1942 that sought to revive them and, for reasons that are clarified, did not prosper. It goes without saying that it seems pertinent to rescue this forgotten experience now that the new Mayan train takes effect.